Use of the task-based approach to strengthen writing fluency in the English language - Tamara Carpio Afonso; Jesús Alberto González Valero; Mallelin Bonachea Rodríguez; Ignacia Rodríguez Estevés (Medisur)
Background: currently there are insufficiencies in strengthening the fluency of the English language, as a foreign language taught in the postgraduate course of Health professionals, since there are limitations in its didactic treatment. Objective: to analyze the benefits of using the task-based approach to strengthen writing fluency in the English language teaching-learning process in postgraduate Health professionals. Methods: pedagogical research that included a group of Health professionals, who completed the English language postgraduate course at the Sancti Spíritus University of Medical Sciences, during the 2020-2021 academic year. Documentary review, class observation, discussion groups, interviews and methodological triangulation. Results: the application of different methods and techniques corroborated that the health professionals presented difficulties in fluency in writing; they spent too much time reviewing ideas; in addition to incurring in unnecessary repetitions, poor syntactic elaboration and writing of short sentences. The use of the task approach was implemented with encouraging results. Conclusion: through the qualitative assessment, the benefits of the task-based approach were evidenced, after its application in the postgraduate course of Health professionals, by favoring the strengthening of fluency in writing the English language